A Internacionalização das Políticas Educacionais nas Cúpulas das Américas - Silva, Jane Machado da (Universidade Federal Fluminense, 2025)
This study aims to show that the agreements reached at the meetings of the Summit of the Americas by the Heads of State and Government, under the aegis of a speech and strengthening cooperation in the hemisphere, function as an internationalization process of the management of national policies. On behalf of integration in the educational field, for example, it creates new markets, of quality standards and develop control mechanisms (through so-called educational indicators) that are intended to guide the teaching productivity and transfer of financial resources to schools. In these terms, given the configuration of the capitalist system and the position of Brazilian the face of international economic policy, one wonders whether the hemispheric cooperation can strengthen solidarity among peoples, respecting the sovereignty of each participating state and the existence of national education policies.